Hypergravity-induced changes in actin response of breast cancer cells to natural killer cells - Minseon Lee (Nature Portfolio, 2021)
Abstract Although immunotherapy holds promising cytotoxic activity against lymphoma or leukemia, the immunosuppressive mechanisms of solid tumors remain challenging. In this study, we developed and applied a hypergravity exposure system as a novel strategy to improve the responsiveness of breast cancer cells to natural killer (NK) cells for efficient immunotherapy. Following exposure to hypergravity, either in the presence or absence of NK cells, we investigated for changes in the cell cytoskeletal structure, which is related to the F-actin mediated immune evasion mechanism (referred to as “actin response”) of cancer cells. Breast cancer cell line MDA-MB-231 cells were exposed thrice to a 20 min hypergravitational condition (10 × g), with a 20 min rest period between each exposure. The applied hypergravity induces changes in the intracellular cytoskeleton structure without decreasing the cell viability but increasing the cytotoxicity of MDA-MB-231 from 4 to 18% (4.5-fold) at a 3:1 ratio (NK-to-target). Analyses related to F-actin further demonstrate that the applied hypergravity results in rearrangement of the cytoskeleton, leading to inhibition of the actin response of MDA-MB-231. Taken together, our results suggest that the mechanical load increases through application of hypergravity, which potentially improves efficiency of cell-based immunotherapies by sensitizing tumors to immune cell-mediated cytotoxicity.